2013
DOI: 10.1155/2013/765352
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of Polycyclic Aromatic Hydrocarbons and Nitro-Derived in Respirable Airborne Particulate Matter Collected from Urban Areas of Rio de Janeiro (Brazil)

Abstract: Air pollution toxic effects are mainly attributed to small inhalable particulates with an aerodynamic diameter of less than 2.5 µm (PM 2.5). Our objective was to investigate mutagenic and clastogenic activity in PM samples collected in Rio de Janeiro. Samples were collected using a high-volume sampler at three sites: with low traffic and (2) and (3) with a heavy traffic. Six polycyclic aromatic hydrocarbons (PAHs) were quantified by gas chromatography/mass spectrometry (GC/MS). Salmonella typhimurium TA98 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 51 publications
2
15
0
3
Order By: Relevance
“…The mutagenic potency of these results is similar to those found in an urban-industrial area, also in the south of Brazil, under the influence of an oil refinery (Lemos, 2011), which varied from 0.27 ± 0.10 to 17.80 ± 2.01 rev/m 3 (TA98) and from 0.47 ± 0.06 to 6.90 ± 0.76 rev/m 3 (TA98 þ S9). Comparing investigations regarding PM2.5 in an area contaminated by wood preservatives (maximum at TA98 24.81 ± 1.83 rev/m 3 ), also located in Triunfo (Coronas et al, 2016), to the urban centers of Porto Alegre (maximum at TA98 24.00 ± 2.55 rev/m 3 ) and Rio de Janeiro (maximum at TA98 56.40 ± 20.60 rev/m 3 ), (Brito et al, 2013;Rainho et al, 2013), our data present less mutagenic activity in these basic strains at 1.37; 1.32 and 3.11 times, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…The mutagenic potency of these results is similar to those found in an urban-industrial area, also in the south of Brazil, under the influence of an oil refinery (Lemos, 2011), which varied from 0.27 ± 0.10 to 17.80 ± 2.01 rev/m 3 (TA98) and from 0.47 ± 0.06 to 6.90 ± 0.76 rev/m 3 (TA98 þ S9). Comparing investigations regarding PM2.5 in an area contaminated by wood preservatives (maximum at TA98 24.81 ± 1.83 rev/m 3 ), also located in Triunfo (Coronas et al, 2016), to the urban centers of Porto Alegre (maximum at TA98 24.00 ± 2.55 rev/m 3 ) and Rio de Janeiro (maximum at TA98 56.40 ± 20.60 rev/m 3 ), (Brito et al, 2013;Rainho et al, 2013), our data present less mutagenic activity in these basic strains at 1.37; 1.32 and 3.11 times, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…PM exposure has also been associated to lung cancer mortality (Gouveia et al, 2003; Junger et al, 2005). The mutagenic and genotoxic activity of PM was associated to polycyclic aromatic hydrocarbons (PAH) found in high traffic stations (Miguel et al, 1990; Ramos et al, 2013). Although these epidemiological links to PM have been established, we do not know of any reports published characterizing toxicological responses of PM from RJ.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration was especially increased for low and intermediate molecular weight PAHs (3-4 rings), such as phenanthrene, fluoranthene, pyrene, benzo(a)anthracene and chrysene, which may quite easily be uptaken by roots (Kipopoulou et al 1999) and possibly cause adverse effects. Phytotoxicity (Somtrakoon and Chouychai 2013) and genotoxicity (Ramos de Rainho et al 2013) of PAHs have been reported previously. In soils located at 6km distance, however, the total content of PAHs was about 50% lower than at 1 km and very similar to the content in the samples taken from 12 to 18 km.…”
Section: Correlation Between Specific Pollutants and Test Plant Respomentioning
confidence: 65%